Profesionalisme Pendidik dalam Peningkatkan Mutu Pendidikan SDN Danau Indah 01 Bekasi - S. Koidatul Awaliah; Astuti Darmiyanti (Universitas Cokroaminoto Palopo, 2022)
The purpose of this study is to find out about the professionalism of educators in improving the quality of education at SDN Danau Indah 01, Bekasi Regency. The research used is using qualitative research methods, with the research instruments used are interviews and observations. The data collection technique used in this research is descriptive technique. The results of the study: First, the professionalism of educators in improving the quality of education at SDN Danau Indah 01 Bekasi Regency can be seen from four competencies, namely: professional competence, social competence, personality competence, and pedagogic competence. Second, there are supporting factors that make professional educators, namely there are two, internal factors and external factors. In addition, there are also inhibiting factors, namely, there are still many educators who do not pursue their profession perfectly, the incompatibility of their educational background with the field being taught, the lack of motivation of educators in improving the quality of education, and the location of the school in the middle of the village. Third, the strategy of educators to overcome the inhibiting factors, namely: approaching stakeholders, attending training, attending workshops, and cultivating literacy.